Penerapan PSAK Nomor 65, PSAK Nomor 22, Dan PSAK Nomor 4 Pada Laporan Keuangan Konsolidasi - Nila Ayu Pratiwi; Refina Pramudya Wardana; Silvia Maharani; Endang Kartini Panggiarti (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
The purpose of preparing these consolidated financial statements is to provide an objective view of the company's financial status and operations. So that interested parties such as investors and auditors understand the condition of subsidiary companies and parent companies. These consolidated financial statements are mandatory when the parent company exercises control over its subsidiary. Methods of data analysis using descriptive qualitative method is a form of descriptive narrative explanation to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, people's thoughts. And for the type of data used in this study using secondary data, namely data taken indirectly. In this study, the secondary data sources were articles, journals on the internet site. The results of this research are that PSAK 22 Revision 2019 regulates consolidated financial statements and provides guidance on presenting consolidated financial statements for parent entities that have subsidiaries, PSAK 65 regulates presentation of consolidated financial statements, and PSAK 4 regulates consolidation.